The impact of TV and magazine on fashion and dressing of urban women of different ages - Wok, Saodah; Mohamed, Shafizan (Department of Media Studies, Faculty of Arts & Social Sciences, University of Malaya, 2008)
The way women adorn themselves and dressed-up reflects the image, status and to a certain extent their inner spirit. For Muslim women, Allah has revealed the verse that mention how women should preserve their aurah and how they should be dressed to reflect their ethical manners. However, present day dressing of some of the urban women particularly the younger groups are very much influenced by the Western fads and fashion trends. Such influence has penetrated the dress culture of the urban Malaysian women of various age groups. Therefore, a study on the impact of television (TV) and magazine on fashion and dressing of Malaysian women of various ages is called for. The objectives of the study are to find out (1) the level of TV and magazine use among Malaysian urban women of various age groups, (2) the level of TV and magazine influence on urban Malaysian women of various age groups, (3) the extent of TV and magazine influence on urban Malaysian women’s fashion and dressing, and (4) the relationship between urban Malaysian women’s fashion and dressing and the use and influence of TV and magazine of various age groups various age groups. The study was conducted among 639 urban Malaysian women using a survey design. Data were collected using questionnaires and the data were analyzed using SPSS WIN 12. Both descriptive statistics and inferential statistics were employed in the study. Results revealed TV influence has an impact on urban Malaysian women’s fashion and dressing. Magazine use is associated with young adult’s fashion and dressing while magazine influence is associated with adolescent’s fashion and dressing.